Simple two-step gelation process to strengthen 3D printed carboxy methyl cellulose gels - Rajput, Tejas; Sathe, Asmi; Gopal, Animesh; Sharma, Aakash; Shanmuganathan, Kadhiravan (Cellulose, 2026)
Carboxymethyl cellulose (CMC) is a water-soluble cellulose ether that is widely utilized in hydrogel applications due to its exceptional water absorption and biocompatibility. This study reports a simple two step strategy to make mechanically robust CMC gels without any additional chemical crosslinkers and how it could be leveraged to strengthen 3D printed CMC gels. These hydrogels, prepared through acid-induced gelation followed by freeze-thawing, exhibited a compressive modulus of 12.4 +/- 0.92 kPa and a compressive strength of 491.0 +/- 18.1 kPa. They could be leveraged for strengthening 3D printing hydrogels of intricate shapes by direct ink writing. Small amplitude oscillatory shear (SAOS) tests indicated an order of magnitude higher storage modulus for freeze-thawed gels (FC) as compared to only acid-induced CMC gels (HCMC). Nonetheless, stress relaxation experiments revealed that FC, as well as HCMC gels, relax at similar time scales. FC gels exhibited clear birefringence under crossed polarizers, indicating molecular ordering that is consistent with the presence of ordered/crystalline domains. Such ordered domains likely contribute to the higher elastic modulus and compressive strength observed in FC gels as compared to HCMC gels.
Keywords: 3D printing; Carboxymethyl cellulose; cellulose; Gels